Ventricular Septal Rupture Complicating Silent Myocardial Infarction - Amr Telmesani; Qasim Al Abri; Mohammed Chamsi-Pasha (Methodist DeBakey Cardiovascular Journal)
A 55-year-old gentleman presented to the emergency department with shortness of breath for the past 3 days. Cardiac magnetic resonance imaging assessed intracardiac shunting and a mechanism of ventricular septal rupture (VSR), showing significant left-to-right shunting and Qp:Qs of 4:1. There was transmural myocardial infarction as well as an aneurysm at the diaphragmatic inferior wall of the left ventricle.